The roots and constructs of Ibn Khaldūn’s critical thinking - Machouche, Salah; Bensaid, Benaouda (IIUM Press, 2015)
Abstract: Many current researches have sought to explore the thought and contributions of Ibn Khaldūn to the various disciplines of human knowledge including philosophy of history, historiography, politics, economics, and education. Little interest, however, is given to his contributions to the theory of critical thinking. This research investigates Ibn Khaldūn’s perspective on critical thinking and critique of intellectual disciplines while exploring its origin and dimensions. The research shows that Ibn Khaldūn’s critical thinking is essentially entrenched in the fundamental vision and origins of Islam, and reflective of the broad Islamic scholarship and the practices of Muslim scholars across the different religious and rational disciplines. What characterises Ibn Khaldūn’s contribution to the field of critical thinking is his ability to apply it across various fields of scholarship yet with a conscious attention to society’s dynamics, particularly the practical dimensions and implications of his theory of human society (‘umrān basharī). Keywords: Critical thinking; Ibn Khaldūn; muqaddimah; ‘umrān; Islamic rationality.